Proposta para formação de professores dos cursos de aprendizagem profissional a partir de demandas da prática pedagógica - Pupo, Matilde Dias Martins (2023)
This is a doctoral research from the Stricto Sensu Postgraduate Program in Education and New Technologies, research line: Teacher Training and New Technologies in Education, from UNINTER Centro Universitário Internacional. It chooses as a basic question: how is the training of teachers who work in professional learning based on teaching practice? The thesis focuses on the training of teachers who work in professional learning courses considering the demands of pedagogical practice. Its general objective is to understand how the training of teachers who work in professional learning courses occurs and, given the demands, to propose a continuing training program from the perspective of teacher professionalization. The qualitative approach methodology was carried out considering the phases: historical context of teacher training for Professional and Technological Education, whose historical configuration occurs in an emergency and unsystematic way without constituting a degree course. For this contextualization, studies by Machado (2013, 2017) and Souza and Rodrigues (2017), among others, were consulted. It followed a study of publications on EPT and includes a contextualization of current professional learning based on the analysis of its regulations. After that, we present a data survey carried out with the participation of teachers of professional learning courses through answers to a questionnaire available on Google Forms and also through unstructured interviews with professionals from the technical team who work in professional learning. Data analysis was based on Content Analysis (Bardin, 2011). The responses were organized and categorized and indicate that teacher training comes from the professional practice of the teachers themselves and their teachers, in addition to studies carried out by themselves. It is highlighted in the research results that professionals who work as teachers in professional learning do not have specific degree training for this type of teaching. As for systematic continued training, it occurs outside the educational system, without institutional support and tends to be linked to conceptual training in technical rationality. So, as an educational product of this thesis, a proposal for a Continuing Training Program for Teachers of Professional Learning Courses was developed from the perspective of teaching professionalization. This proposal can be used by other institutions in the training of their teachers, as many of the proposed contents permeate the specificity of Professional Learning.